MOF-808: A Metal–Organic Framework with Intrinsic Peroxidase-Like Catalytic Activity at Neutral pH for Colorimetric Biosensing - Zheng, He-Qi; Liu, Chun-Yan; Zeng, Xue-Yu; Chen, Jin; Lü, Jian; Lin, Rong-Guang; Cao, Rong; Lin, Zu-Jin; Su, Jin-Wei (Inorganic chemistry, 2018)
Natural enzyme mimetics with high catalytic activity at nearly neutral pH values are highly desired for their applications in biological systems. Herein for the first time a stable MOF, namely MOF-808, has been shown to possess high intrinsic peroxidase-like catalytic activity under acidic, neutral, and alkaline conditions. As a novel peroxidase mimetic, MOF-808 can effectively catalyze the oxidation of 3,3′,5,5′-tetramethylbenzidine when H2O2 serves as oxidant, accompanied by a significant color variation in the solution. The catalytic activity and the color variation were greatly dependent on H2O2 concentration, and thus MOF-808 can be applied to the colorimetric sensing of H2O2. The H2O2 detection limit is 4.5 μM, and the linear range is 10 μM to 15 mM. In view of the significant inhibition effect produced by ascorbic acid, a facile and sensitive approach for colorimetric sensing of ascorbic acid was successfully established. The AA detection limit is 15 μM, and the linear range is 30–1030 μM. Further investigation found that the catalytic activity of MOF-808 could be mainly ascribed to the Zr–OH(OH2) groups. Such active Zr–OH(OH2) groups can be effectively shielded by gluconic acid, and subsequently the catalytic activity of MOF-808 was significantly suppressed. With these findings, a facile and selective colorimetric assay for glucose sensing has been successfully explored via combination of the glucose oxidation with the TMB oxidation. The glucose detection limit is 5.7 μM, and the linear range is 5.7–1700 μM. MOF-808 is one of the best colorimetric biosensors among the peroxidase mimics reported for H2O2, AA, and glucose detection.